Nomophobia (No MObile PHone PhoBIA) Among Medical Students: A Literature Review - Sri Wahyuni (International Journal of Engineering, Science and Information Technology, 2022)
Smartphones have become more popular due to advances in high-speed Internet connectivity. Smartphones are popular among young people, including medical students, as virtual devices. As a result, excessive use of smartphones has expressed concerns about its addictive potential, a condition known as nomophobia. Nomophobia (No MObile PHone PhoBIA) is the worry or fear people feel when they do not have their mobile phone or are unable to use it. The term was introduced in 2008 and is considered a modern phobia. Nomophobia is also a general pathology among students, particularly those in medicine. This literature review examines the prevalence of nomophobia, symptoms, causes of nomophobia among medical students, and the impact of nomophobia on student achievement. Existing literature on nomophobia in the PUBMED and Google Scholar databases was examined using the search terms ‘nomophobia’ OR ‘mobile phone use’ OR ‘mobile phone addiction’ AND 'medical students.' Several studies have found that medical students have nomophobia. More than 50% of medical students in this review have moderate nomophobia, while 5-20% have severe nomophobia. The most common symptoms of nomophobia were anxiety, agitation, tachycardia, inability to turn off the mobile phone, constantly checking the phone, charging the battery even when the phone is nearly fully charged, fear of not being able to connect to a data network, concerns about being removed from online status or identity, and avoid activities to spend time on a mobile device. Students with severe nomophobia reported poor academic performance; students with a higher level of nomophobia performed poorly academically and vice versa. Medical students had a greater incidence of addiction to mobile phones, which affected their health and academic achievement. More emphasis should be placed on early detection and intervention to overcome nomophobia.